Peran Humas dalam Program Corporate Social Responsibility untuk Mengembangkan Program Rumah Jahit (Sangkrini) (Studi Deskriptif pada Humas PT Pembangkitan Jawa Bali Up Muara Karang) - Muhamad Thorique Rizki; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
PT PJB UP Muara Karang has a social responsibility to create corporate business sustainability by supporting the creation of social sustainability and preserving the environment. Therefore, the PR of PT PJB UP Muara Karang carries out a social activity program, namely integrated sewing houses as a source of income in Muara Angke. This study seeks to determine the Role of PT PJB UP Muara Karang's Public Relations in its Corporate Social Responsibility Program to Develop the Sewing House Program (Sangkrini). In this study, the authors employed a descriptive qualitative research method, utilizing informants as data sources, and interviewing procedures to obtain data. Interviews were conducted with three informants, including the Public Relations CSR officer of PT PJB Up Muara Karang and the CDO of Muara Karang. The results indicate that the role of public relations has performed admirably and optimally in delivering benefits for the moms in the Muara Angke region so that they can earn their own money and receive support in the field of community empowerment.